(untitled) (Research, Society and Development, 2020)
Nowadays, new methodologies have been used to complementing and assisting in the fixation of knowledge. So, the aim of this work was apply a active education methods using a study case methodology to assess the critical competence in objective and subjective assessments and self-assessment, and to analyze the results obtained in a qualitative way. Students developed content, presented seminars, evaluate their peers objectively (assigning grades) and subjective (selecting according to preference) and also performed the self-assessment. Based on the grades attributed by the students, the ability to evaluate by peers by comparing variances was evaluated. From the results obtained, we can conclude that there is a mutual influence on the two types of evaluations used in this research. Students were able to evaluate their peers and also self-evaluation. There is consistency between different evaluators and also when compared to self-criticism. From the research on the experience of active teaching, it is possible to observe the growing preference of students for this teaching methodology.